Adsorption activity of raw material of perspective marsh-water plants of Western Siberia - N. V. Kelus; L. G. Babeshina; S. Ye. Dmitruk; N. S. Subbotina; L. A. Nikiforov (Бюллетень сибирской медицины)
In order to find effective sorbents of herbal origin, we’ve studied adsorption properties of aerial dry raw materials of 31 marsh-water, medical perspective, plant species. It was found that 8 of those 31 exercises adsorption activity (Shpagnum species).